FACING THE CHALLENGES AND OPPORTUNITIES IN STARTING A BUSINESS IN THE TECHNOLOGICAL ERA - Sartika Sartika; Muhammad Syukur; Firdaus W Suhaeb; Ansyaruddin Ansyaruddin (Sean Institute, 2023)
In this digital era, there is an evolution in technological developments in media technology, call it new media or people often call it online media or people more familiarly call it the internet. This media is also said to be a media that until now no one has matched the growth in the number of users. In developed countries, new media beats various media that were previously used as reference sources in obtaining information. The term new media emerged in the 20th century. Our discussion of the challenges and opportunities in building a business in the technological era is divided into several stages: (1) Entrepreneurial Opportunities and Challenges in the Information Technology Era; (2) E-Commerce Development; (3) Positive and Negative Impacts of e-commerce; (4) The Role of the Media; (5) Effective and Efficient Tips for Developing a Business in the Digital Era. Technology is seen as a strategy to strengthen competitive advantages and as support for a company's competitive strategy in facing competitors. Increasing global competition in all fields makes Information Technology (IT) a necessity that cannot be abandoned. The increasingly rapid development of information technology has given rise to e-commerce application software in the business world which can support cutting the distribution chain so that consumers can obtain a product at a cheaper price.